Chemical–Physical, Sensory Analyses and Consumers’ Quality Perception of Local vs. Imported Loquat Fruits: A Sustainable Development Perspective - Riccardo Testa; Giuseppina Migliore; Giorgio Schifani; Ilenia Tinebra; Vittorio Farina (Agronomy, 2020)
Local products and their distribution through short supply chains play a key role in the sustainable development of many rural areas, as affirmed by the 2030 Food and Agriculture Organization of the United Nations (FAO) Agenda. Moreover, in the last years, more and more consumers have shown a specific interest towards local production, pushed by the need for healthy eating, protecting the environment, and boosting the local economy. However, the cultivation of local fruit varieties or ecotypes has considerably decreased in the last decades because of their low production potential. As a result, many farmers have been forced to replace local orchards with few worldwide grown cultivars, causing a loss of genetic agrobiodiversity. For instance, in Italy, the loquat market is composed of imported cultivars and local grown autochthonous fruits (ecotype). Therefore, the aim of this study is to analyze the chemical–physical and sensory qualities, as well as the determinants of Italian consumer preference towards local ecotype of loquat fruit compared to imported varieties. Results show that local ecotypes result in excellent physico-chemical and sensory attributes, and that place of purchase and taste are the most important factors influencing consumers’ preference towards local loquats. Therefore, the cultivation of loquat ecotypes, together with effective marketing strategies, could increase the competitiveness of certain Italian rural areas, where this crop has always played a significant role in the economy.